Studi Etnofarmasi Tumbuhan Berkhasiat Obat pada Masyarakat di Kecamatan Mamosalato Kabupaten Morowali Utara Sulawesi Tengah - Masyita, Andi Atirah; Ibrahim, Nurlina; Pettalolo, Nur Bahra (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Mamosalato sub-district empirically utilizes medicinal plants to treat diseases that have been passed down from generation to generation. This study aims to determine the local wisdom possessed in treating diseases, recognize the types and parts of plants used to treat diseases, know how to process, use, dose and duration of use of plants to treat diseases. This type of research uses descriptive research with qualitative methods. The sampling technique is purposive sampling with open-ended interviews to 7 informants using a questionnaire media. Based on the results of the study, there are 35 types of plants that are obtained as medicine using different parts, ways of utilization and usage of each plant. The conclusion of this study is that the parts of plants that are often used are leaves 63%, roots 7%, stems 5%, tubers 2%, fruit 9%, seeds 2%, flowers 7% and all parts of the plant 5%. Processing methods include boiled 64%, kneaded 10%, pounded 8%, squeezed 5%, filtered 8%, soaked 2% and brewed 3%. The way to use it is drunk 82%, affixed 8%, applied 5% and dripped 5%. The rules of use are 1 to 3 times a day and the duration of use is 1 to 30 days starting from the onset, reduction to the disappearance of symptoms or declared cured. Diseases that can be treated using medicinal plants are 24 diseases.